Media, Islamic religious authority and the imagination of ummat in Indonesia - Rahman, Taufiqur (Universitas Muhammadiyah Yogyakarta, 2015)
This article investigates the history of Islamic religious authority in Indonesiaand the role of the media in the development of religious authority and the imagination of Islamic community. The old traditional authority of local imam or Islamic clerics is now being challenged by transnational interpreters of Islam with the availability of direct connection with Islamic clerics and religious learning resources from the Middle East, the United States, the United Kingdom or anywhere else in the world facilitated by the internet. The article argues that the media play a significant role in the current understanding of ummat and Islamic religious authority in the global and local contexts. By employing the method of discourse analysis the article also argues that the contestation of Islamic religious authority has contributed to the process of re-imagination and re-conceptualisation of the concept of global Muslim ummat by Muslim groups in Indonesia.